The Measures of Efficiency of Power Generation Plants in Sylhet of Bangladesh - Kanis Fatama Ferdushi; Anton Abdulbasah Kamil; Saleh Ahmed; Luthful Alahi Kawsar (International Journal of Mathematics and Mathematical Sciences)
This study measures the performance of power generation plants in Sylhet region of Bangladesh considering twenty-four-month monthly dataset during 2013-14. To measure the performance of those plants, gross electricity generation was considered as output for the stochastic frontier model, whereas fuel consumption, lube oil consumption, auxiliary consumption, cost, heat rate, and hours of run were considered as input variables. Based on the log-likelihood hypothesis test, trans-log production model is preferred over Cobb–Douglas (C-D) production model for this study. The average efficiency of the selected plants is above 90 percent, and there is Sylhet Combined Cycle Power Plant (CCPP) which has an efficiency of about 78.6 percent for truncated normal distribution. In the time-variant inefficiency effects model, fuel consumption, cost, square product of lube oil consumption, interaction between fuel consumption and lube oil consumption as well as auxiliary consumption, and hours of run have a significant positive influence on power generation. On the other hand, some input variables such as hours of run and interaction between cost and heat rate have a significant negative influence on power generation. The estimated values of the time-varying inefficiency parameter η are positive for both the truncated and the half-normal distribution. This result indicates that technical efficiency has declined over the reference period of the study.